A Taxonomy of Arts Interventions for People With Dementia. (6th March 2019) - Cousins, Emily; Tischler, Victoria; Garabedian, Claire; Dening, Tom
Abstract: Background and Objectives: The current evidence base for the arts and dementia has several limitations relating to the description, explanation, communication, and simplification of arts interventions. Research addressing these challenges must be multidisciplinary, taking account of humanities and science perspectives. Consequently, this research aimed to produce a taxonomy, or classification, of arts interventions for people with dementia as a contribution to this growing field. Research Design and Methods: This research was underpinned by taxonomy and realist methodology. Taxonomy, the science of classification, produces a common language to name, define, and describe the world around us. Realist theory explains how interventions "work" and produce their effects. The main findings in this paper were generated from a case study and a Delphi study. Results: An arts and dementia taxonomy of 12 dimensions was developed: Art Form, Artistic elements, Artistic focus, Artistic materials, Arts activity, Arts approaches, Arts facilitators, Arts location, Competencies, Complementary arts, Intervention context, Principles. Discussion and Implications: Arts interventions can be classified according to their contexts, mechanisms, and outcomes. A range of stakeholders could benefit from the taxonomy, including people with dementia, artists, practitioners, carers, care staff, funders, commissioners, researchers, and academics. Language relating to the arts and dementia can be adapted depending on the audience. This is a foundational model requiring further development within the arts and dementia community.